Towards Understanding Home Grown School Feeding Programme and its Institutional Framework and Roles in Nigeria: A Holistic Approach - Dr. Olofu Paul Agbade; Niyi Jacob Ogunode; Usua Oku Bassey (Journal of Research in Innovative Teaching and Inclusive Learning, 2023)
This work is titled: towards understanding school feeding programme and its institutional framework and roles in Nigeria: A holistic approach. The purpose of the paper was to provide a comprehensive write-up on Nigerian homegrown school feeding programme. Therefore, this work provided an extensive discussion on the concept of school feeding programme in general. Also discussed herein was aims and objectives of Nigerian homegrown school feeding programme. The historical development of Nigerian homegrown school feeding programme was also exhaustively captured. Also explicated in this work were the types of school feeding from different dimensions, the legal framework of school feeding programme as well as the institutional framework and roles of school feeding programme in the context of Nigeria. The challenges of school feeding programme was also identified; while offering recommendations for improvement of the programme.